LITERASI FINTECH, KEPERCAYAAN KONSUMEN DAN NIAT MENGGUNAKAN E-WALLET - Retno Damayanti; Nurhidayah Nurhidayah (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2022)
This study aims to examine the role of FinTech literacy and trust on the intention of using e-wallet. The sample is 84 respondents who use at least 3 times a month one of the e-wallet applications. The 5-point Likert scale was used to determine respondents' responses to the question items contained in the questionnaire. The collected data was then analyzed using the SPSS program. The results show that FinTech literacy is not a factor that is considered by Generation Z to use e-wallet applications. However, trust in e-wallet is a factor that can increase the interest of Generation Z to continue using e-wallet applications. Next, this paper will be able to contribute to the development of behavioral financial science.